Comparative Phase Evolution, Morphological and Optical Analysis of Partially Stabilized Zirconia Ceramics - COJAN, Claudia Andreea; BARABÁS, Réka; MUREȘAN-POP, Marieta; BIZO, Liliana (Studia Universitatis Babeș-Bolyai Chemia, 2024)
Partially stabilized zirconia (PSZ) ceramics are one of the most important materials used for different applications like thermal barrier coatings, refractories, oxygen-permeating membranes, and dental and bone implants. In this work, the structural, morphological, and optical properties of bulk Mg-PSZ, Ca-PSZ, and Ce-PSZ, prepared by solid state reaction at high temperature, were comparatively evaluated. Laser diffraction analyses revealed particles by thousands orders of magnitude larger compared to crystallite sizes determined from X-ray powder diffraction (XRPD), more evidenced in the case of Ca-PSZ. The structural analyses indicated the presence of both m- and t-ZrO2 phases, in different ratios, depending on the doping cation. The scanning electron microscopy (SEM) micrographs confirmed the homogenous distribution of the elements through mixed oxides. Further, optical properties evaluated in terms of ultraviolet–visible diffuse reflectance spectroscopy (UV-VIS DRS) revealed that the doped ZrO2 samples showed a smaller bandgap compared with pure ZrO2, which may be due to the incorporation of magnesia, calcia or ceria in the ZrO2 matrix. The maximum bandgap reduction of ZrO2 was observed on Ca-PSZ, having a value of 3.52 eV